Impacto da temperatura sobre a eficiência de inoculação com Azospirillum brasilense na cultura do milho - Lima, Charleston dos Santos (2021)
Growth promote bacteria of plants have currently gaining prominence, with significant increase in commercial inoculants for non-leguminous crops, with the purpose of reducing costs with nitrogen fertilizers, increasing tolerance to factors that promote stress and increasing productivity. However, success in the use of technology can be affected by numerous factors related to genotype, bacterial strain and environmental condition, putting the use of technology in the field in doubt. Thus, the objective of the research was to evaluate the influence of temperature in laboratory conditions and field in the efficiency of the inoculation process with Azospirillum brasilense, based on growth, biochemical, nutritional and grain yield variables. The fist experiment was developed at the Laboratory of Plant Physiology of Plants of Agrobiological Interest - UFSM Santa Maria. Seeds of two corn hybrids Syn 488 and Syn 505, inoculated or not, were placed on germitest paper moistened 2.5 times the weight of the substrate and placed to germinate in B.O.D type equipment for a period of seven days. After this period, the seedlings were collected and the variables germination, first count, root length, shoot length, dry seedling weight, biochemical variables (superoxide dismutase (SOD) and peroxidase (POD) enzymes, hydrogen peroxide content and lipid peroxidation), and photosynthetic pigments (total chlorophylls and carotenoids) were determined. Additionally, in second experiment, the corn hybrids (inoculated or not) were tested in the field at three sowing time (8, 15 and 18 hours), being determined the temperature and relative humidity of the soil at the time of sowing. Subsequently, in the flowering, were evaluated the responses of the interaction (inoculation x time) for biochemical variables, photosynthetic pigments, concentration of nutrients in the tissues, productivity and crude protein of the grains. It was evidenced that under controlled conditions, the hybrid Syn488 demonstrated a negative effect of inoculation, with high lipid peroxidation in plants exposed to the bacteria A. brasilense, which was not verified in the field. On the other hand, Syn505 showed an increase in growth parameters and intense modulation of photosynthetic pigments and POD and SOD enzymes, mainly under temperatures of 25 and 30 °C. When the hybrids were sown in the field, both genotypes responded positively to the inoculation, however, the sowing time changed the responses of the bacterium, obtaining satisfactory results from the plant-bacterial interaction when the sowing was carried out at 15 and 18 hours in first season, with higher POD and SOD activity, nitrogen concentration and grain yield. It is concluded that seed inoculation can be influenced by the temperature to which seeds and microorganisms are exposed, even for a short period of time, which can limit the responses of the bacteria via an increase in the enzymatic system, biological nitrogen fixation and nutrient absorption.